Multivariate Statistical Analysis Reveals the Heterogeneity of Lacustrine Tight Oil Accumulation in the Middle Permian Jimusar Sag, Junggar Basin, NW China - Yuce Wang; Jian Cao; Keyu Tao; Xiuwei Gao; Erting Li; Chunhua Shi (Geofluids)
Tight oil and gas accumulation commonly has heterogeneities within the reservoir formation. This heterogeneity, however, is hard to investigate by conventional geological and (organic) geochemical tools and thus is critical and challenging to study. Here, we attempted multivariate statistical analysis to reveal the heterogeneity based on a case study in the lacustrine tight oil accumulation in the middle Permian Lucaogou Formation of the Jimusar sag, Junggar Basin, NW China. Clustering heat maps and multi-dimensional scaling analysis revealed the heterogeneity of tight oil accumulation. The heterogeneity is reflected by the complex relationship between the two reservoir sweet spots as well as the oil migration and accumulation vertically and spatially, rather than the previous thoughts that it is a closed system associated with proximal hydrocarbon accumulation patterns. Multiple biomarkers show that the source rocks and reservoirs have similar characteristics in the lower part of the formation, reflecting a proximal hydrocarbon accumulation pattern in the lower sweet spot (near-source accumulation, abbreviated as NA). This represents a relatively closed system. However, the upper sweet spot and the middle section mudstone sequence intervening the two sweet spots are not a completely closed system in a strict sense. These sequences can be divided into three tight oil segments, i.e., lower, middle, and upper from deep to shallow. The lower segment is sited in the lower part of the middle section mudstone sequence. The middle segment is composed of the upper part of the middle section mudstone sequence and the lower part of the upper sweet spot. The upper segment is composed of the upper part of the upper sweet spot and the overlying upper Permian Wutonggou Formation reservoirs. Oils generated in the lower segment migrated vertically to upper sweet spot reservoirs through faults/fractures, and laterally to distal reservoirs. Oils generated in the middle segment were preserved in reservoirs of the upper sweet spot. Oils in the upper segment require accumulation by vertical and lateral migration through faults/fractures. As such, the tight oil accumulation is complex in the Lucaogou Formation. From base to top, the accumulation mechanisms in the Lucaogou Formation were NA, VLMA (vertical and lateral migration and accumulation), NA and VLMA, thereby showing strong heterogeneities. Our data suggest that these processes might be typical of tight oil accumulations universally, and are important for future exploration and exploitation in the region to consider the heterogeneities rather than a closed system. The multivariate statistical analysis is an effective tool for investigating complex oil-source correlations and accumulation in petroleum basins.